Effect of Lactiplantibacillus plantarum P16 on Relieving DSS-induced Ulcerative Colitis - Zhixian CHEN; Qian CHENG; Yan ZHANG (Shipin gongye ke-ji)
Objective: To investigate the therapeutic effect of Lactiplantibacillus plantarum P16 on dextran sulfate sodium (DSS)-induced ulcerative colitis in mice. Methods: BALB/c male mice were randomly divided into 4 groups (n=10): control group, model group, L. plantarum P16 group, and LGG group. The experiment lasted for 14 d, with the first 7 d of normal water intake followed by 7 d of free access to 3.5% DSS solution for the model, P16, and LGG to induce ulcerative colitis (UC). Throughout the experiment, the control and model groups were orally gavaged with 0.2 mL/d of saline, while the P16 and LGG groups were orally gavaged with 0.2 mL/d of the corresponding probiotic suspension at a concentration of 5×109 CFU/mL. Disease activity index (DAI) was evaluated, colon tissue pathology was observed by HE staining, and inflammatory factors (TNF-α, IL-1β, IL-6, IL-10) in serum were measured by ELISA. Additionally, 16S rRNA sequencing was used to analyze changes in the intestinal microbiota of mice and study the effects of P16 on colitis. Results: Compared with the control group, L. plantarum P16 reduced the DAI index in colitis mice significantly (P<0.0001), alleviated colon length shrinkage, and reduced DSS-induced damage to colon tissues. L. plantarum P16 effectively regulated inflammatory factors TNF-α, IL-6, and IL-1β in mice (P<0.01). Furthermore, L. plantarum P16 improved the alpha diversity of the intestinal microbial community in mice. L. plantarum P16 intervention adjusted the ratio of Firmicutes and Bacteroidetes in the intestinal microbiota of mice, increased the relative abundance of Akkermansia, and decreased the relative abundance of Helicobacter and Colidextribacter, thus improving the balance of the gut microbiota. Conclusion: L. plantarum P16 has the potential to alleviate ulcerative colitis in mice and effectively regulate the intestinal microbiota balance in colitis mice.